FROM CONFLICT TO ALTERNATIVE SOLUTION: A CASE STUDY OF LOCAL INHABITANTS’ RESISTANCE TO TIN MINING IN SELINDUNG VILLAGE, BANGKA BARAT - Sarpin Sarpin; Ibrahim Ibrahim; Herza Herza (Berumpun: International Journal of Social, Politics, and Humanities, 2021)
The sea and the cost with the abundant resources frequently become the competition among the groups of interest. The competition is close to the conflict and ends up with the physical and verbal violence. Selindung village located in the coast area of Muntok, West Bangka is the area of the abundant resources, marine biota, and tin commodity. The contradiction of the economic interest causes the emerge of longer conflict. This study aims to map these conflicts and offers to the best alternative to cope with. This study is a qualitative research with the interview and observation strategy as the data collection. The result of the conflict mapping shows that the conflicted area shows the social tension. The pro and anti tin mining groups clash each other with the company interest, the local government, and the impact of the local people’s occupation interfere that causes a conflict. The conflict itself has experienced up and down however the various tin mining moduses stand still. The conflicts that have been mapped are the competition of resource access, the social jealousy, the policy of the maritime politics that does not accommodate the fishermen’ interest, as well as the issue of identity. There are four alternatives to get over these conflicts by referring to Galtung’s perspective namely supporting the role of government to be more accommodating and communicative to the majority interest, ensuring no extending licence of a large scale mining in the future, mediating by having two neutral parties, and finding new economic alternative to the local people who have already been depended on the mining activity.